2019
DOI: 10.1002/lt.25442
|View full text |Cite
|
Sign up to set email alerts
|

Home‐Based Exercise in Patients Awaiting Liver Transplantation: A Feasibility Study

Abstract: Frailty is associated with increased mortality both before and after liver transplantation (LT). There are no standardized exercise programs, in particular home‐based exercise programs (HBEPs), for patients awaiting LT. The aim was to investigate the feasibility of such a program in patients awaiting LT. Patients were randomly selected from the Birmingham LT waiting list and provided with a 12‐week HBEP, including average daily step (ADS) targets and twice‐weekly resistance exercises. Feasibility was based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
133
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 74 publications
(135 citation statements)
references
References 41 publications
1
133
1
Order By: Relevance
“…This has important implications for the development of effective rehabilitation strategies to treat sarcopenia in children after LT. Recent evidence in adults with cirrhosis and sarcopenia indicate that the utilization of resistance exercise to treat sarcopenia is a safe, feasible, and effective method to elicit improvements in muscle strength . Evaluation of this approach as a potential rehabilitation strategy is warranted in children with sarcopenia.…”
Section: Discussionmentioning
confidence: 99%
“…This has important implications for the development of effective rehabilitation strategies to treat sarcopenia in children after LT. Recent evidence in adults with cirrhosis and sarcopenia indicate that the utilization of resistance exercise to treat sarcopenia is a safe, feasible, and effective method to elicit improvements in muscle strength . Evaluation of this approach as a potential rehabilitation strategy is warranted in children with sarcopenia.…”
Section: Discussionmentioning
confidence: 99%
“…Within the 11 exercise studies reported in CLD, several generic (SF‐36, EQ‐VAS) and disease‐specific (Chronic Liver Disease questionnaire, CLDQ) questionnaires have been utilised with variable findings (Tables and ). Improvements in vitality ( P = .01 (SF‐36)), perceived general health status ( P = .03 (SF‐36)), physical activity (+1.24 points (CLDQ)) and fatigue (+0.80 points (CLDQ)) were reported with exercise interventions, but interestingly in the two home‐based exercise intervention study from Canada and the UK, no improvements were seen in either generic HRQoL or anxiety and depression scores . This may be due to the lack of regular, supervised medical professional interactions or due to the fact that participants included in these studies were dealing with the ongoing burden of more advanced, decompensated cirrhosis whilst on the transplant‐waiting list.…”
Section: Physical Exercise In Patients With Chronic Liver Diseasementioning
confidence: 97%
“…Whether the changes in 6MWT in the Williams study are due to the intervention or to a “learning effect” is difficult to discern, as the study lacked repeat baseline assessments of the 6MWT . In support, further studies undertaken at home have found significant improvements in average daily steps and incremental shuttle walk test (ISWT) ( P < .01 for both outcomes) following a 12‐week exercise intervention consisting of walking and body‐weight resistance exercises (2‐3‐times weekly). These findings demonstrate that costly equipment may not be required to produce positive improvements in aerobic capacity and function for patients with CLD.…”
Section: Physical Exercise In Patients With Chronic Liver Diseasementioning
confidence: 98%
See 1 more Smart Citation
“…As with efforts to enhance muscle mass in other wasting conditions, empiric interventions to improve physical performance through exercise, nutrition, pharmacotherapy, and behavioral support have been used . Williams et al in the current issue of Liver Transplantation assess the value of a home‐based exercise program (HBEP) …”
mentioning
confidence: 99%